ZAMANAGÓY BILIMLENDIRIWDE MODULLI – KREDIT SISTEMALARÍ HAQQÍNDA - Prenov, B.B.; Atabaeva, B.J. (ILIM hám JÁMIYET, 2020)
The article is devoted to the description of the modular credit system of teaching and its advantages in modern education.